2021
DOI: 10.1371/journal.pone.0245388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of salt intake reduction on CVD mortality in Costa Rica: A scenario modelling study

Abstract: Cardiovascular diseases (CVD) represent the leading cause of death in Costa Rica and high blood pressure was associated with a mortality rate of 29% in 2018. The average household sodium intake in the country is also two times higher than the World Health Organization recommendation. The objective of this study was to estimate the impact of reducing salt intake on CVD mortality in Costa Rica using a scenario simulation model. The Preventable Risk Integrated ModEl (PRIME) was used to estimate the number of deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Researchers from Costa Rica and Brazil both received face-to-face training on the use of PRIME from the Université Laval, followed by two webinars. The findings from this research were published [ 46 , 47 , 48 , 49 ], and used to form strong arguments with policy decision makers on setting upper limits on sodium in food products. In addition to the data generated, the capacity built can be applied towards the creation of health and economic data related to other public health priorities.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers from Costa Rica and Brazil both received face-to-face training on the use of PRIME from the Université Laval, followed by two webinars. The findings from this research were published [ 46 , 47 , 48 , 49 ], and used to form strong arguments with policy decision makers on setting upper limits on sodium in food products. In addition to the data generated, the capacity built can be applied towards the creation of health and economic data related to other public health priorities.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicate that the risk of suffering from hypertension or suffering from some complication is greater. Simulation studies carried out in Latin America have estimated that reducing sodium consumption as recommended by the WHO could reduce about 47,000 deaths from cardiovascular diseases, mainly from coronary, hypertensive, and cardiovascular disease, the equivalent of 85 million dollars in health care [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The economic losses in productivity attributable to excessive sodium intake have been estimated at more than 700 million dollars 30. In Costa Rica, based on the recommendations of the WHO and a National strategy for the comprehensive approach of non-communicable diseases and obesity, Vega-Solano et al simulated scenarios reducing the average salt intake of that country (9 g/day) by 46% and 15%, respectively 31. It was observed that, even in the modest reduction (15%), 5% of CVD deaths could be avoided, while in the ideal scenario (46%), 2.5 times more deaths could be avoided (13%).…”
Section: Discussionmentioning
confidence: 99%